Hierarchical COK-X Materials for Applications in Catalysis and Adsorptive Separation and Controlled Release - Pulinthanathu Sree, Sreeprasanth; Breynaert, Eric; Kirschhock, Christine E. A.; Martens, Johan A. (Frontiers in Chemical Engineering, 2022)
Over the years, COK has developed a family of silicate materials and metal–organic framework hybrids with hierarchical porosity and functionality, coined zeogrids, zeotiles, and COK-x (stemming from the Flemish name of the laboratory “Centrum voor Oppervlaktechemie en Katalyse”). Several of these materials have unique features relevant to heterogeneous catalysis, molecular separation, and controlled release and found applications in the field of green chemistry, environmental protection, and pharmaceutical formulation. Discovery of a new material typically occurs by serendipity, but the research was always guided by hypothesis. This review provides insight in the process of tuning initial research hypotheses to match material properties to specific applications. This review describes the synthesis, structure, properties, and applications of 12 different materials. Some have simple synthesis protocols, facilitating upscaling and reproduction and rendering them attractive also in this respect.